The contribution of phonological knowledge, memory, and language background to reading comprehension in deaf populations - Hirshorn, Elizabeth A.; Dye, Matthew W. G.; Hauser, Peter; Supalla, Ted R.; Bavelier, Daphne (Frontiers in Psychology, 2015)
While reading is challenging for many deaf individuals, some become proficient readers. Yet we do not know the component processes that support reading comprehension in these individuals. Speech-based phonological knowledge is one of the strongest predictors of reading comprehension in hearing individuals, yet its role in deaf readers is controversial. This could reflect the highly varied language backgrounds among deaf readers as well as the difficulty of disentangling the relative contribution of phonological versus orthographic knowledge of spoken language, in our case ‘English’, in this population. Here we assessed the impact of language experience on reading comprehension in deaf readers by recruiting oral deaf individuals, who use spoken English as their primary mode of communication, and deaf native signers of American Sign Language. First, to address the contribution of spoken English phonological knowledge in deaf readers, we present novel tasks that evaluate phonological versus orthographic knowledge. Second, the impact of this knowledge, as well as verbal short-term memory and long-term memory skills, on reading comprehension was evaluated. The best predictor of reading comprehension differed as a function of language experience, with long-term memory, as measured by free recall, being a better predictor in deaf native signers than in oral deaf. In contrast, the measures of English phonological knowledge, independent of orthographic knowledge, best predicted reading comprehension in oral deaf individuals. These results suggest successful reading strategies differ across deaf readers as a function of their language experience, and highlight a possible alternative route to literacy in deaf native signers.